Microbial colonization and decomposition of commercial tea and native alder leaf litter in temperate streams - Ferreira, Verónica (2022)
Leaf litter decomposition in streams is a fundamental ecosystem process that allows for the cycling of nutrients. The rate at which leaf litter decomposes is greatly controlled by its intrinsic characteristics. However, intraspecifc variation in leaf litter characteristics poses a major challenge for large-scale studies aiming at identifying the environmental moderators of leaf litter decomposition. Thus, several standardized organic substrates have been proposed as surrogates for leaf litter. Tea bags were proposed as a standardized alternative to leaf litter for studies in soil and their use in aquatic ecosystems has been growing in recent years. It is therefore necessary to evaluate how tea is colonized and decomposed by aquatic microbial decomposers to assess its usefulness as a surrogate for leaf litter in litter decomposition studies. Here we compared the microbial colonization (based on the reproductive activity of aquatic hyphomycetes) and decomposition of green and rooibos teas and native alder leaf litter in two streams difering in environmental conditions. Colonization of green tea was lower than that of alder leaf litter, but their decomposition rates were similar. In contrast, colonization of rooibos tea was similar to that of alder leaf litter, but it decomposed 3–4×slower. Results were consistent in both streams. Despite diferences in magnitude, dynamics of microbial colonization and decomposition of tea were similar to those of alder leaf litter and were sensitive to substrate characteristics. Tea may be used as a surrogate for leaf litter in studies addressing microbial-driven leaf litter decomposition in streams.